Genetic Polymorphism Of The System Of Natriuretic Peptides And Long-Term Results Of Coronary Artery Stenting - Daminov Botir Pulatovich, Alyavi Bakhrom Ansixonovich, Azizov Shukhratjon Ismatdjonovich (International Journal of Advanced Science and Technology, 2020)
Materials methods. The study included 158 patients with coronary heart disease with angina pectoris of FC III-IV tension (women 34 - 21.52%). Upon inclusion in the study, all patients underwent: Echocardiography, TLC, genotyping of 6 genes of the system of natriuretic peptides, coronary angiography and stenting of the coronary arteries. For follow-up examination, patients were invited after a year. The study included echocardiography, TLC, stress echocardiography.